Reproductive biology of Illex coindetii and Todaropsis eblanae (Cephalopoda: Ommastrephidae) off Northwest Africa (4°N, 35°N) - Hernández-García, Vicente (2002)
From 1352 Illex coindetii and 713 Todaropsis eblanae obtained from the by-catches of trawlers fishing off Northwest Africa (4°03′N, 34°40′N), body size at sexual maturity and spawning seasons were estimated. An approximation to the potential reproductive output was estimated for female and male Illex coindetii and for male Todaropsis eblanae. For Illex coindetii, in both sexes, sexual maturity occurred at a wide range body size. However both, range and size at maturity for both sexes decreased from north to south. The maturing and spawning periods were extended to the whole year, although they seemed to take place with higher intensity during the spring-summer in the northern and central zones, but during autumn at the Gulf of Guinea. The difference in temperature between the different zones may be the main physical condition influencing the inter-zonal differences. Significant correlation between spermatophore mean size and DML was observed. The highest number of spermatophores was 1412. The potential fecundity in females was estimated to be over 729,000 oocytes. The maximal number of spermatangue groups was six, and the highest number of spermatangues observed was 1996. High genetic diversity should be expected in the progeny of one female I. coindetii after they mate with several males. For T. eblanae, sexual maturity in females occurred at a larger size than in males. The estimated sizes at maturity were 168 and 130 mm DML for females and males respectively. Two main spawning seasons were observed, the first in spring and the second in autumn-winter. The highest number of spermatophores was 269 (the mean number was 100). Mature males can be recognised by having as maximum 1 sucker, and no less than 4 ridges in the right row of the fourth right arm.